Sosialisasi Pola Asuh Anak dan Remaja di Era Digital (PAAREDI) - Harianto Harianto; Zulin Nurchayati; Alfiana Yuniar Rahmawati (Universitas Tarakanita, 2025)
This Community Service (PkM) activity is motivated by the phenomenon of technologyaddiction such as gadgets, social media, the internet and online games among children andteenagers. This phenomenon is a new challenge that parents as part of the closest family mustpay attention to. Parents need to adapt to changes in the digital era and understand emergingtrends in order to optimize balanced parenting. Therefore, PkM with the theme